(untitled) (Journal of Humanities and Social Sciences Research, 2022)
The triple jump is a leaping event in the sports program that is popular at the local, Arab, and international levels. It is one of the activities that necessitate a high level of skill, as well as the ability to link some physical abilities, such as agility, with other physical traits. The research challenge was summarized in designing specific workouts for students that contribute to building agility and understanding the technical stages of the triple jump, because effectiveness demands physical prerequisites and abilities, the most significant of which is agility. The research community included 32 students from Al-Qasim Green University’s College of Physical Education and Sports Sciences, and 18 students were chosen as a research sample after rejecting students who practiced for effectiveness and who were not devoted to permanence and failure. After executing tribal tests and statistical transactions, the sample proportion for study was 53 percent of the overall community. The researchers concluded that the workouts contribute to the development of agility and learning the triple jump for the female students in the research sample based on the pre- and post-test and data tabulation. For the second step, the researchers proposed that these exercises be implemented in educational units and during athletics lessons.